Organic Solar Cells: Problems and Perspectives. (3rd June 2010) - Chidichimo, G.; Filippelli, L.
Abstract : For photovoltaic cells to convert solar into electric energy is probably the most interesting research challenge nowadays. A good efficiency of these devices has been obtained by using inorganic semiconductor materials. On the other hand, manufacture processes are very expensive in terms of both materials and techniques. For this reason organic-based photovoltaic (OPV) cells are attracting the general attention because of the possible realization of more economical devices. Organic materials are abundant and easily handling. Unfortunately OPV cells efficiency is significantly lower than that of inorganic-based devices, representing a big point of weakness at the present. This is mainly due to the fact that organic semiconductors have a much higher band gap with respect to inorganic semiconductors. In addition, OPV cells are very susceptible to oxygen and water. In this paper we will describe some of the different approaches to the understanding and improving of organic photovoltaic devices.